Thrombophilia abnormalities in recurrent pregnancy loss - Thiruchelvam, A.; Sekaran, M. (Scientific Publishers India, 2010)
Recent evidences associate thrombophilia with adverse pregnancy outcome. Numerous studies confirm Factor V Leiden (FVL) and Prothrombin G20210A (PT G20210A) mutations as important thrombophilia risk factors in Caucasians. However, these mutations are rare in Asians and thrombophilia investigations are therefore considered irrelevant in these patients. Hence, the status of thrombophilia-induced recurrent pregnancy loss (RPL) in Asians is obscure and poorly understood. Four-hundred and two (402) Malaysian RPL-subjects and 160 parous-controls, who are part of the Asian community, were investigated for FVL, PT G20210A, Methylene Tetrahydrofolate Reductase C677T (MTHEFR C677T), activated protein C resistance (APCR), protein C (PC), protein S (PS), antithrombin (AT) and antiphospholipid antibodies. One-fifth of the RPL-subjects were identified to have thrombophilia abnormalities. Acquired Thrombophilia was more prevalent in Malaysian RPL-subjects compared to the inherited form in Caucasians. FVL and PT G20210A mutations were identified in 2.0% of the RPL-subjects, disputing the rarity of these mutations in Asians. The overall findings warrant the need to review thrombophilia investigations and its corresponding management (the use of anticoagulant therapy) in thrombophilia-induced RPL patients of Asian origin.